Antarctic science-policy interface: a way forward - Ramirez Buchheister, Gustavo Alejandro (My University, 2021)
SCAR SC-HASS Action Group on PoLSciNex originally planned to convene a session at the 2020 SCAR Open Science Conference (OSC), to which several interesting abstracts were submitted.11. SCAR’s Stand...
Keywords: Scar tissue